Assessment of DNA damage in children exposed to indoor tobacco smoke - AKICI, AHMET (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2010)
The present Study is aimed to evaluate the possible DNA damage in children who are living with smoker parents. The tests were conducted by Using alkaline comet assay, measured as a percentage of DNA damage in tail (%DNA(T)). The children that participated in the study were selected from the pediatric Unit of a hospital in Istanbul, Turkey. %DNA(T) was significantly higher (p < 0.01) in children who were exposed to indoor tobacco smoke (10.73 +/- 1.38) compared to the children in the control group (8.16 +/- 1.29). The number of cigarettes consumed by household members did not seem to affect the severity of the DNA damage. Since children spend most of their time at home and cannot remove themselves from harmful living conditions this important genotoxic finding should be considered by smoker parents for the future health consequences of their children. (C) 2009 Elsevier GmbH. All rights reserved.
Keywords: DNA damage; Indoor tobacco smoke; Children; Comet assay; GENETIC-DAMAGE; ENVIRONMENTAL-POLLUTANTS; HUMAN-LYMPHOCYTES; SCE ANALYSIS; COMET ASSAY; BIOMARKERS; MOTHERS; HEALTH; HOMES